Propuesta para manejo y disposición de residuos del municipio de Muzo, Boyacá (2019)
This work presents a technical summary of the elaboration of the proposal for solid waste treatment in Muzo, Boyaca, during 2016. The diagnosis of waste management panorama was realized, including the results of characterization. about 25 tons of solid waste per week were produced; 63.7% of which were organic waste. 17.21% valuable waste; and 4.74% high complexity waste. After that, the best option for each type is selected according to the real conditions of location, by means of diffuse TOPSIS technique (technique for order performance by similarity to ideal solution). Finally, the definitive proposal is presented, focused to the recovery.